DAMPAK PENERAPAN TRANSAKSI E-COMMERCE MELALUI PEMUNGUTAN PAJAK PENGHASILAN (PPh) - Suprihatin, Neneng Sri; Afriyanti, Mukhlisah (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Â .This study aims to analyze the implementation of income tax collection (PPh) on e-commerce transactions at KPP Pratama Pandeglang. as well as what obstacles are experienced in implementing Taxation on e-commerce transactions. The study was conducted using descriptive qualitative methods. The population of the study was 180,896, and 60 samples were taken, using the purposive sampling method. Data collected by questionnaire and observation methods, analyzed in detail. The results of the study can be concluded that: 1) Tax collection uses the Self Assessment System method, 2) Constraints in e-commerce tax collection are the e-commerce business people who have not been maximized, socialization has not been done thoroughly and e-commerce transactions that are difficult in the detection of a form of business which has its own problem, namely the difficulty of the government to establish clear and fair tax regulations.